Pembelajaran Bahasa Arab Menggunakan Smart Apps Creator Untuk Kelas VII Madrasah Tsanawiyah - Massofia, Fitrah Dinanti; Khoirunnisa, Dyah Ayu; Dinanti, Syintia Dwi; Huda, Miftahul; Rahmawati, Rahmawati (UIN Maulana Malik Ibrahim Malang, 2023)
Arabic language has so far been considered conservative because it is only taught by kyai in Islamic boarding schools, does not have an elite place in national education system. So that in order to support student success in learning Arabic language, of course teacher must have various kinds of media used, aiming to make students easy on what they learn. One of the strategies to improve learning is by using Smart Apps Creator. This study use a qualitative approach with library research method with data sources taken from the exploration of literature related to study of learning Arabic and analyzed in depth through data triangulation; data reduction, data presentation and conclusion. The results of the research are that learning Arabic for middle-level VII grade students does not only rely on books that are difficult for students, but also be created using interactive media with the Smart App Creator. Because learning through Smart App Creator can help teachers and students learn Arabic language better and more fun.